Analysis of the Effect of Product Quality, Price Perception and Social Value on Purchase Decisions for Lampung Tapis Fabrics - Septiyana, Fenny; S. Shihab, Muchsin; Kusumah, Hendra; Sugina; Apriliasari, Dwi (Pandawan, 2023)
Consumer purchasing decisions are an important factor in determining the existence of a product. Galeri Kalianda is a business engaged in the fashion sector providing tapis fabric, which is a woven fabric originating from the Lampung area. The purpose of this study was to determine the variable product quality (X1), perceived price (X2), and social and cultural values (X3) that influence the purchase decision of tapis lampung fabric (Y). The sampling technique used the Simple Random Sampling method with (n = 60) who had made purchases and users of the Lampung filter cloth at the Kalianda Gallery, Jakarta. Based on multiple linear regression analysis, the model Y = 0.570 + 0.136 (x1) +0.299 (x2) +0.223 (x3) + ε is obtained. The T test shows that the variables of product quality, price perception, and social and cultural values partially have a positive and significant effect on purchasing decisions. While the F test shows that these three variables together have an effect of (R2 = 59.5%) on purchasing decisions. The conclusions from the study entitled